Shikonin inhibits proliferation and induces apoptosis in glioma cells via downregulation of CD147 - Guo, Na (Mol Med Rep, 2019)
Shikonin, a traditional Chinese medicine, has been identified as being capable of inducing apoptosis in various tumors, including glioma, and is thus considered to be a promising therapeutic agent for tumor therapy. However, little is known about the molecular mechanism of shikonin in glioma. The present study investigated the influence of shikonin on the proliferation and apoptosis of glioma cells U251 and U87MG and explored the potential molecular mechanisms. It was identified that shikonin was able to induce apoptosis in human glioma cells in a time- and dose-dependent manner, and a decreased expression level of cluster of differentiation (CD)147 was observed in shikonin-treated U251 and U87MG cells. Knockdown of CD147 inhibited U251 and U87MG cell growth, whereas CD147 overexpression enhanced cell growth and decreased shikonin-induced apoptosis. Additionally, an increased expression level of CD147 suppressed the elevated production of reactive oxygen species and mitochondrial membrane potential levels induced by shikonin. The data indicated that shikonin-induced apoptosis in glioma cells was associated with the downregulation of CD147 and the upregulation of oxidative stress. CD147 may be an optional target of shikonin-induced cell apoptosis in glioma cells.